2011
DOI: 10.1021/jo200638k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5-Iodopyrrolo[1,2-a]quinolines and Indolo[1,2-a]quinolines via Iodine-Mediated Electrophilic and Regioselective 6-endo-dig Ring Closure

Abstract: The endo-cyclic ring closure of 1-(2-(substituted ethynyl)phenyl)-1H-pyrroles 3a-t and 1-(2-(substituted ethynyl)phenyl)-H-indole 4a-o mediated by Lewis acid (I(2)) under mild conditions afforded substituted 5-iodopyrrolo[1,2-a]quinolines 5a-t and 5-iodoindolo[1,2-a]quinolines 6a-o in good to excellent yields. The reaction shows selective C-C bond formation on the more electrophilic alkynyl carbon, resulting in the regioselective 6-endo-dig-cyclized product. Iodo derivatives of pyrrolo- and indoloquinolines al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…53 The reaction progressed by the coordination of I 2 with an acetylene bond of substrate 112 to form an iodonium complex, 113 which undergoes intramolecular nucleophilic attack by the C-2 of pyrrole and indole on the activated triple bond to form iodo-substituted quinoline 114 (Scheme 38). 53 The reaction progressed by the coordination of I 2 with an acetylene bond of substrate 112 to form an iodonium complex, 113 which undergoes intramolecular nucleophilic attack by the C-2 of pyrrole and indole on the activated triple bond to form iodo-substituted quinoline 114 (Scheme 38).…”
Section: Scheme 37mentioning
confidence: 99%
“…53 The reaction progressed by the coordination of I 2 with an acetylene bond of substrate 112 to form an iodonium complex, 113 which undergoes intramolecular nucleophilic attack by the C-2 of pyrrole and indole on the activated triple bond to form iodo-substituted quinoline 114 (Scheme 38). 53 The reaction progressed by the coordination of I 2 with an acetylene bond of substrate 112 to form an iodonium complex, 113 which undergoes intramolecular nucleophilic attack by the C-2 of pyrrole and indole on the activated triple bond to form iodo-substituted quinoline 114 (Scheme 38).…”
Section: Scheme 37mentioning
confidence: 99%
“…[9] Considering the wide range of biological activities, developing efficient synthetic methods of indolizines has attracted wide attention in the fields of organic chemistry and chemical biology. [10] The majority for the preparations of indolizines include Tschitschibabin reaction, [11] 1,3-dipolar cycloaddition, [12] 1,5-dipolar cycloaddition, [13] I 2 -mediated oxidative cyclization, [14] transition-metal-catalyzed intramolecular cyclization [15] and intermolecular cyclization. [16] To the best of our knowledge, oxidant and solvent were proven to switch the regio-selectivity for the annulation reaction of 2alkyl pyridines with cinnamic acids by copper catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we found that the reaction of aldehyde with various indoles in the presence a catalytic amount of iodine produced the corresponding bisindole in high yields. On the other hand, recently, Verma and his co‐workers have reported the synthesis of indolo[1,2‐ a ]quinolines via (6‐ endo‐dig ) iodocyclization using molecular iodine 7d. Moreover, recently, Enders and co‐workers observed the formation of seven‐membered (7‐ endo‐dig ) fused tetracyclic azulene derivatives using a gold catalyst 4c.…”
Section: Introductionmentioning
confidence: 99%